Bacterial biofilm in adenoids of children with chronic otitis media. Part II: a case–control study of nasopharyngeal microbiota, virulence, and resistance of biofilms in adenoids. (3rd March 2020) - Jacquier, Hervé; Vironneau, Pierre; Dang, Huong; Verillaud, Benjamin; Lamers, Gerda; Herman, Philippe; Vicaut, Eric; Tessier, Natacha; Bidet, Philippe; Varon, Emmanuelle; Van Den Abbeele, Thierry; Cambau, Emmanuelle; et al.
Abstract: Background : We previously described that adenoid tissue in children with chronic otitis media (COM) contained more mucosal biofilms than adenoid tissue removed for hypertrophy. Aims/objectives: The aim of the second part was to characterize nasopharyngeal microbiota and explore virulence of the most common middle ear pathogens. Material and methods : Bacteriological analysis was performed following a culture-based approach on the samples recovered from 30 patients of COM group (15 biofilm-positive and 15 biofilm-negative) and from 30 patients of a control group (15 biofilm-positive and 15 biofilm-negative). Virulence factors of Streptococcus pneumoniae, Streptococcus pyogenes, and Haemophilus influenzae were investigated. Results : The most frequent species were Firmicutes followed by Proteobacteria and Actinobacteria . The presence of biofilm was statistically associated with an increase of the number of bacterial species and Firmicutes phylum regardless of the condition (case/control). No virulence factors associated with invasive isolates were found for the most common middle ear pathogens. Conclusions and significance : This case–control study demonstrated that the presence of COM plus biofilm was associated with a given microbiota which contained more Firmicutes. Our study allows a better understanding of physiopathological mechanisms involved in chronic otitis media and paves the way for further investigations.